Unexpected Covariant Behavior of the Aegean and Ionian Seas in the Period 1987–2008 by Means of a Nondimensional Sea Surface Height Index. Issue 10 (24th October 2017) - Reale, M.; Salon, S.; Crise, A.; Farneti, R.; Mosetti, R.; Sannino, G.
Abstract: In this work, we use a set of recent multiyear simulations to develop a simplified sea surface height index (SSH). The index characterizes the dynamics of Ionian upper layer circulation and its links with sea surface height and salinity in the Southern Adriatic and Aegean Seas during the period 1987–2008. The analysis highlights a covariant behavior between Ionian Sea and Aegean Sea associated with a mutual zonal exchange of water masses with different salinity characteristics. Our analysis confirms that the variability observed in the period 1987–2008 in the upper layer circulation of the Ionian was driven by the salinity variability in the Southern Adriatic and Aegean Sea. This study supports and reinforces the hypothesis that two observed BiOS‐like reversals reflect the existence of multiple equilibrium states in the Mediterranean Thermohaline circulation in the Eastern Mediterranean and that a complete characterization of observed variability needs to take into account a fully coupled Adriatic‐Ionian‐Aegean System. Key Points: The reversals in the Ionian Sea reflect the existence of multiple states in the Thermohaline circulation in the Eastern Mediterranean Aegean and Ionian Seas explicitly show a covariant behavior in the period 1987–2008 The source of this covariant behavior relies on substantial zonal exchanges of salinity between the two basins